MODEL OF INTENTION TO USE E-HEALTH APPLICATION (MOBILE JKN) DURING THE COVID-19 PANDEMIC IN THE SPECIAL CAPITAL REGION OF JAKARTA - Akhmad T, Ramadhan; Didik J, Rachbini (Dinasti International Journal of Management Science, 2021)
This study aims to analyse the relationship between Perceived Ease of Use, Perceived Usefulness, Social Influence and Attitude to Intention to Use. This study also examines the mediating effect of Attitude on Perceived Ease of Use, Perceived Usefulness, Social Influence and Intention to Use. The study involved 384 users of Mobile JKN application. Researchers used Partial Least Square (PLS) as the technique to analyse measurements and structural models. The results of this study indicate that Perceived Usefulness and Social Influence do not have a significant effect on Intention to Use but Attitude has a significant influence in mediating the relationship between Perceived Ease of Use, Perceived Usefulness and Social Influence on Intention to Use. For theoretical and practical implications, researchers need to test Intention to Use with other variables, and the marketers need to pay attention to users who already have the habit and the experience of using e-health applications to maintain their retention.